The regulatory challenges of innovative customized combination products - Reis, Mariana E.; Bettencourt, Ana; Ribeiro, Helena M. (Frontiers in Medicine, 2022)
Abstract Background/Aims: Combination products are therapeutic and/or diagnostic products that can combine drugs and medical devices and which increasing complexity has raised new regulatory framework challenges. To reach the market, a combination product must be classified based on the principal mode of action (PMOA). However, research and technological progress has been leading to the development of novel combination products with no clearly defined PMOA, emphasizing the lack of a systematization process, thus challenging the correct classification of these products. To illustrate the regulatory challenge, two case studies are discussed: innovative combination products with PMOA that can change due to an external stimulus, specifically custom-made 3D-printed scaffolds with incorporated medicinal substances. Methods: Data was collected through computational search engines, regulatory agencies and equally relevant associations. The analysis of the data resulted on this state-of-the-art review, a description of the decision-making process by the regulatory authorities, and case studies analysis that culminated in the proposal of a decision-tree scheme. Findings: Current regulations do not fully address complex combination products namely personalized 3D-printed scaffolds. Two merged regulatory approaches are suggested along with the schematization of the rational assisted by a decision-tree tool. Conclusion: Combination products have become increasingly sophisticated, which has furthered the need to develop multidisciplinary collaborations within the health sector to adapt to these innovative healthcare solutions as well as with regulators to overcome the challenges posed for their classification.